The British Economy: A Growth and Employment Miracle? - Andrew Glyn (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2005)
First paragraph: Since 1990 the UK economy has grown at 2.4 percent per year, compared to 1.7 percent in the Eurozone. The growth differential in favour of the British economy, previously regarded as the »sick man of Europe«, has even been increasing. Since 2000 the UK has grown twice as fast as the Eurozone's 1.2 percent per year. As a result the UK labour market looks distinctly healthier than Europe's. Both the UK and Euroland had around ten percent unemployment in the early 1990s. But UK unemployment has been around five percent since 2001 whilst in Europe it has been has fluctuating around nine percent. In the UK around 73 percent of the working age population are in work, as compared to 65 percent in the EU-15. Moreover provision of jobs in the UK has not been at the expense of improvements in productivity, the basic determinant of the long-term growth of living standards. Since 2000 labour productivity in the UK business sector has been growing about 1.5 percent per year, around three times the rate of advance in Europe.
Keywords: 330